Quality of agri-food products in Europe (Club de Bruxelles BrusellesBE)
Focusses on the Community's approval to the agri-food industry; the background to community law; the free movement of agri-foodstuffs, and the main priorities for the Single Market programme. Discusses the Single Market legislative provisions and reviews the Community's efforts to define and introduce a strategy for promoting quality in the agri-food industry. Considers the Commission's decision to guarantee quality via the protection of geographic indications, labels of origin, and the introduction of certificates of specific character of foodstuffs. Reviews quality controls and consumer safety aspects, particularly in the light of the call for an European Food Agency.
DC